Early school‐age cognitive performance post–pediatric heart transplantation. (26th October 2020) - Gold, Anna; Bondi, Bianca C.; Ashkanase, Jenna; Dipchand, Anne I.
Abstract: Background: As survival in pediatric heart transplantation (HTx) has improved due to medical advances, the analysis of long‐term outcomes impacting quality of life such as cognition and development becomes increasingly important. Neuropsychological assessments provide a comprehensive understanding of individual needs, allowing for the development of tailored recommendations and interventions. Methods: Routine neuropsychological assessment was completed between 5 and 7 years of age in this cohort of pediatric HTx recipients at our center (Jan 2014‐Oct 2018), including tests of general intellect (WPPSI‐IV, WISC‐V), academics (WIAT‐II/III), perceptual‐motor abilities (Beery VMI), and memory (CMS). Relevant medical variables were collected. Results: Among 25 children, the median age at testing was 6.7 (IQR:5.8‐7.4) years, with a median time since HTx of 5.2 (IQR:4.8‐6.8) years. Medical diagnoses included congenital heart disease (CHD; 56%) and cardiomyopathy (44%). Cognitive functioning across the intellectual, academic, and perceptual‐motor domains fell within the low‐average range, while memory abilities fell within the average range. DSM‐5 clinical diagnoses were provided for 14 (56%) children: Intellectual Disability‐Mild (20%), Learning Disability (20%), Language Disorder (8%), and Attention‐Deficit/Hyperactivity Disorder (12%). The presence of neurological issues and/or CHD predicted poorer performance on various neuropsychological domains. Conclusions: Over 50% of this cohort of pediatric heart transplant recipients seen for routine post‐HTx neuropsychological assessment received a clinical psychological diagnosis, notably higher than rates in the general population. This population requires monitoring to ensure that high risk children are identified and successfully supported in school and their community.